Strategi Pengembangan Pembelajaran Tahfidz Harian untuk Optimalisasi Hafalan Juz ‘Amma Siswa MDTA Al Azhar Tapus - Citra Aulia Putri; Hikmah Hayati; Sularno Sularno (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This study aims to develop an effective daily tahfidz learning strategy to improve Juz ‘Amma memorization among MDTA students. The problems identified include inconsistency in daily recitations, lack of review activities, and limited teaching methods. A qualitative approach was applied using observation, interview, and documentation techniques. The strategies implemented consisted of daily verse recitation, weekly review, peer learning, and a reward system. The results showed an average improvement of 30% in students’ memorization within one semester. Moreover, students’ motivation and discipline also increased. This study further emphasizes that tahfidz is not merely about memorizing, but also about forming consistent learning habits. The daily routine approach helps students build discipline, peer collaboration, and self-confidence. Consequently, tahfidz programs need to integrate structured and innovative learning methods to achieve sustainable improvement.